The Application of a Problem-Based Learning Model to Enhance Student Engagement in Pancasila and Civic Education Classes - Nurhidayah, Nurhidayah; Murdiono, Mukhamad (Ridwan Institute, 2026)
The purpose of this study is to analyze and describe the implementation of problem-based learning (PBL) in increasing student learning participation in Pancasila and Citizenship Education subjects. The research employed a mixed-methods approach, combining qualitative and quantitative methods. The study was conducted in class VIII C of SMP Negeri 1 Mlati, Sleman, Yogyakarta. Data were collected through observation, documentation, and questionnaires. The results show that the problem-based learning model is able to increase student learning participation, with the highest score reaching 76.7%. This result meets the criteria for the